Whale-watch vessel noise levels with applications to whale-watching guidelines and conservation. (December 2021) - Arranz, Patricia; de Soto, Natacha Aguilar; Madsen, Peter T.; Sprogis, Kate R.
Abstract: The number and size of whale-watching and swim-with-cetacean vessels are increasing worldwide, but the noise impact on targeted species depends on vessel source characteristics, which remain largely unquantified. Here, we report the acoustic characteristics from 13 whale-watching vessels from Australia and Canary Islands. Acoustic recorders were deployed to measure the frequency-weighted sound levels (for low [LF], mid [MF] and high frequency [HF] cetacean hearing types) of motor sailing, catamarans, and motor vessels operating at 4–8 kn representing the slow speed of whale-watch scenarios. The highest estimated source levels (SLs) were recorded from large catamarans with inboard engines (LF = 160 ± 3, MF = 148 ± 2, HF = 146 ± 2 dB re 1 µPa m). The lowest SLs were from smaller motor vessels and particularly by a hybrid vessel powered by electrical outboard engines (LF = 140 ± 3, MF = 136 ± 2, HF = 134 ± 2 dB re 1 µPa m). We demonstrate that at the same speed and distance, different vessels may produce very different received levels to the animals. To reduce disturbance to cetaceans we recommend tourism vessels meet a broadband (0.2–10 kHz) SL limit of <150 dB re 1 µPa (RMS) when within 500 m of cetaceans. Graphical Abstract: ga1 Highlights: Whale-watch vessels spend targeted and potentially large time close to whales. Noise from whale watch-vessels is the primary driver of disturbance. Vessel source third octave level below 120 dB re 1 µPa will ensure a low noise induced impact. Development of an international low noise certification of whale-watching vessels is needed.